(untitled) (Journal of NELTA, 2022)
One of the most affected sectors during the COVID-19 pandemic was education. Abrupt and sudden changes in teaching and learning practices that teachers and students experienced were unprecedented, and the effect is still felt today. Hence, the study sought to identify the challenges secondary English language teachers in Bangladesh, Malaysia and Nepal faced during the pandemic. Adopting a Comparative Case Study (CCS) research model, this was a transnational effort to explore the experiences of a cross-border ELT professional community teaching under various restrictions and limitations imposed by the governments in response to the ongoing COVID-19 pandemic. Five key challenges emerged during the findings, namely: (i) teaching and learning dificulties, (ii) unreliable and invalid assessments, (iii) infrastructural hurdles in a home learning environment, (iv) student displacement, and (v) compromised teacher wellbeing. In retrospect, there was a cause for optimism as teachers acquired crucial survival skills, yet most challenges remain valid to this day. So various stakeholders must remain vigilant and devise robust measures in anticipation of future events of this kind and scale.